Heat transfer conewall jet - Исaтaев, М.С.; Сүйінжaновa, Ұ.П.; Исмaилов, A.Х.; Сейдуллa, Ж.Қ.; Ильясовa, Г.О. (Хабаршы. Физика сериясы, 2016)
The purpose of this work to investigate experimentally the effect of the Reynolds number, the parameter of the transverse curvature of the cone and the opening angle on local heat transfer coefficients in the divergent and convergent turbulent semi-infinite jet, spreading over the surface of the cone. Experimental study of heat transfer coefficient were carried out at the local angles of the cone opening ω = 15,00; 90.00. Studied jet parameters resulting from the nozzle with a protruding rectangular segment with the parameters elongation λ = 2,04; 4.77 and 9.85. During the experiments were considered the influence of the local heat transfer coefficient near the wall on the setting of the transverse curvature in the direction of the jet on the initial and final number of Reynolds. The results showed that in the diverging jet (ω = 15,00) at a height between 10-14 caliber growth is observed in the beginning, and then a uniform decrease local heat transfer coefficient.